The Impact of Digital Transformation in Banks on Economic Growth: A Study of a Sample of Countries from 2012 to 2021 - Mecerhed, Bilel; Guettar, Fatima Zohra (The journal of contemporary issues in business and government, 2023)
This study aims to highlight the relationship between digital transformation indicators in the banking sector and economic growth for a sample of countries. Three panel models were employed: the aggregate model, fixed-effects model, and random-effects model. After individually estimating each model, statistical tests were applied in the empirical study. The study concludes that the random-effects model is the most effective, indicating a direct and positive impact of digital transformation indicators in the banking sector on economic growth.